IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN PAI - Jennifer Abelia; Iwan Hermawan; Nur Hasan (STAI Ihyaul Ulum Gresik, 2026)
Contemporary education requires a learning approach that is not limited to mastering theory. Instead, students must be taught to demonstrate creativity, problem solving, and practical skills. The Project Based Learning (PjBL) learning model places students at the center of the learning process and actively engages them in completing projects that are relevant to the real world. This model involves students in the process of exploration, research, and application of knowledge in real-world contexts. Direct interviews were conducted with SDN Karawang Kulon III regarding the implementation of the PjBL learning model in Islamic Religious Education learning, including Islamic Religious Education teachers, students, and the principal as a supervisor. The results of the interviews conducted by the researcher can describe how the implementation of the Project Based Learning learning model in Islamic Religious Education learning at SDN Karawang Kulon III. This model creates a learning atmosphere that focuses on students to be more proactive, motivated, and develop creative learning abilities, real projects in Islamic Religious Education classes prepare students to face difficulties and opportunities in the future.